Internet Addiction and its Relationship with Anxiety, Stress, Depression and Insomnia in Nursing and Midwifery Students - Reza Noori; Naeimeh Sadeghyan (Kerman University of Medical Sciences, 2017)
Background & Objectives: Internet addiction is one of the problems associated with the advancement of technology that affects people's mental health. The aim of this study was to investigate the relationship between addiction to the Internet and insomnia, anxiety, depression and stress in nursing and midwifery students of Bojnourd Islamic Azad University in 2017. Methods: This descriptive-analytical study was conducted on 250 nursing and midwifery students of Bojnourd Islamic Azad University selected through stratified random sampling. Data collection was done using demographic information, Young's Internet addiction, Insomnia (ISI), and Depression, Anxiety and Stress Questionnaire (DASS21). Data were analyzed using statistical test of one-way ANOVA and through SPSS-16 software. Results: In whole, 76% of students were female and 53.2% were nursing students. Mean score of Internet addiction was 31.14 and 6.7% of students had Internet addiction. Also, mean scores of anxiety, stress, depression and insomnia were respectively 12.54, 23.37, 17.12 and 14.56. Addiction to the Internet showed a significant relationship with anxiety, stress, depression and insomnia (P˂0.001). Conclusion: Because of the obtained prevalence rate for Internet addiction among students, and its significant relationship with depression, anxiety, stress and insomnia in them, adequate planning for preventing this health problem is highly recommended. Keywords: Internet addiction, Depression, Insomnia, Anxiety, Stress Citation: Noori R, Sadeghyan N. Internet Addiction and its Relationship with Anxiety, Stress, Depression and Insomnia in Nursing and Midwifery Students. Journal of Health Based Research 2017; 3(1): 51-57.